Flow characteristics around a circular cylinder undergoing vortex-induced vibration in the initial branch - Hsieh, Shih-Chun (2018)
Vortex-induced vibration (VIV) has been studied extensively and much attention has been devoted to the “lock-in” phenomenon, which is primarily responsible for fatigue damage to structures. Nevertheless, the behavior of the surrounding flow can also be important. This paper investigates the flow characteristics of the wake in the initial branch for a vibrating cylinder using a new PIV technique capable of a high sampling rate of 200 Hz. The experiments were carried out over a wide range of reduced velocities to better understand the important trends. The mean velocities and turbulence characteristics were obtained by ensemble averaging repeated velocity measurements. This study reveals new insights on the flow characteristics of the wake in the initial branch. In particular, the cylinder vibration is found to lead to the formation of oblique jets, which have a profound influence on the mean flow velocity, turbulence intensity, formation and convection of the vortices, and variations to the stagnation and separation points of the cylinder during vibration.